2017
DOI: 10.1016/j.actaastro.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Historical space steps of Turkey: It is high time to establish the Turkish space agency

Abstract: This paper discusses the importance of space in today's space driven world, the current space activities of Turkey, its space organizations with legislation background information and calls for the necessity for the establishment of the Turkish Space Agency (TSA). Firstly, the importance of space is given which is followed by a brief background and current space activities in Turkey. Then, the answers to why Turkey needs a National Space Agency are outlined by stating its expected role and duties. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been suggested that Türkiye's Antarctic policy forms part of a broader ambition of expanding Turkish political, economic, scientific and humanitarian influence globally (Adnan 2021, Yanık & Karaoğuz 2021, Bilgic 2022. This is further evidenced by Türkiye's interest in the Arctic through its recent applications for Observer Member status to the Arctic Council (which have so far been unsuccessful) and its decision to ratify the Svalbard Treaty (Çetin & Büyüksağnak 2021, Limon 2021, Pedersen 2021, Wenger 2022) and more broadly by its increasing development of outer space research and technology though the establishment of the Turkish Space Agency (Ercan & Kale 2017, González Levaggi & Blinder 2022 The information presented in this study confirms that Türkiye is no longer a 'watching' non-Consultative Party but, since 2013, has taken active steps towards the demonstration of substantial scientific research activity within the continent. Other non-Consultative Parties that may also be well placed to attain consultative status, at some point in the future, include Canada, Portugal, Switzerland, Malaysia, Colombia, Venezuela and Belarus (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Türkiye's Antarctic policy forms part of a broader ambition of expanding Turkish political, economic, scientific and humanitarian influence globally (Adnan 2021, Yanık & Karaoğuz 2021, Bilgic 2022. This is further evidenced by Türkiye's interest in the Arctic through its recent applications for Observer Member status to the Arctic Council (which have so far been unsuccessful) and its decision to ratify the Svalbard Treaty (Çetin & Büyüksağnak 2021, Limon 2021, Pedersen 2021, Wenger 2022) and more broadly by its increasing development of outer space research and technology though the establishment of the Turkish Space Agency (Ercan & Kale 2017, González Levaggi & Blinder 2022 The information presented in this study confirms that Türkiye is no longer a 'watching' non-Consultative Party but, since 2013, has taken active steps towards the demonstration of substantial scientific research activity within the continent. Other non-Consultative Parties that may also be well placed to attain consultative status, at some point in the future, include Canada, Portugal, Switzerland, Malaysia, Colombia, Venezuela and Belarus (Table II).…”
Section: Discussionmentioning
confidence: 99%